The assessment of fish consumption by university students of different academic profiles - Kula, Sławomir; Śmiechowska, Maria (Nauki Inżynierskie i Technologie Engineering Sciences and Technologies, 2016)
Fish are one of the basic food products which is considered as a valuable source of protein. Therefore, the low consumption rate of fish and processed fish products in Poland, which is about 13 kg per person, is alarming. The purpose of this study was to diagnose the factors influencing the consumption of fish and processed fish products by young Poles studying on different faculties and entering their adult age. The study has shown that 40% of medical students have declared fish consumption several times a month, whereas 17% of technology students and 15% of humanities students have declared the same. Students prefer to eat fish in the form of fillet and canned fish. Culinary preferences, health value and the price have been the most common factors taken into account while choosing a particular fish
International Journal of Food Science and Bioprocessing, 2016, Nr 1 (1), s. 67-76
Keywords: fish; consumption assessment; students; ryby; ocena spożycia; studenci